The Financial Implications of the Coronavirus COVID-19 Pandemic: A Review - Nusratullin, Ilmir; Mrochkovskiy, Nikolay; Yarullin, Raul; Zamyatina, Natalia; Solntseva, Oksana (Cuestiones Políticas, 2021)
The COVID-19 pandemic in 2020 was a real shock to the entire global community. It hit both the health systems of the infected countries and the economies. Border closures, quarantines for citizens and disruption of production caused economic shock to many organizations. First, the tourism and transport industry suffered, followed by agriculture and mining, and then all other industries. However, the economic crisis also caused some problems in the financial sector: increased risks of non-compliance with loans, cash outs of bank deposits, increased pressure on the insurance market, panic in commodity and securities markets. The purpose of this study is to examine the impact of COVID-19 on the financial system of developed countries. As part of this study, a review of scientific research in the field of pandemics and finances was conducted, how the spread of infection affected the economy, banking, financial markets, and government regulation in the financial sector as a whole.